Linkage to HIV care after home‐based HIV counselling and testing in sub‐Saharan Africa: a systematic review. Issue 7 (22nd May 2017) - Ruzagira, Eugene; Baisley, Kathy; Kamali, Anatoli; Biraro, Samuel; Grosskurth, Heiner; ,
Abstract: Background: Home‐based HIV counselling and testing (HBHCT) has the potential to increase HIV testing uptake in sub‐Saharan Africa (SSA), but data on linkage to HIV care after HBHCT are scarce. We conducted a systematic review of linkage to care after HBHCT in SSA. Methods: Five databases were searched for studies published between 1st January 2000 and 19th August 2016 that reported on linkage to care among adults newly identified with HIV infection through HBHCT. Eligible studies were reviewed, assessed for risk of bias and findings summarised using the PRISMA guidelines. Results: A total of 14 studies from six countries met the eligibility criteria; nine used specific strategies (point‐of‐care CD4 count testing, follow‐up counselling, provision of transport funds to clinic and counsellor facilitation of HIV clinic visit) in addition to routine referral to facilitate linkage to care. Time intervals for ascertaining linkage ranged from 1 week to 12 months post‐HBHCT. Linkage ranged from 8.2% [95% confidence interval (CI), 6.8–9.8%] to 99.1% (95% CI, 96.9–99.9%). Linkage was generally lower (<33%) if HBHCT was followed by referral only, and higher (>80%) if additional strategies were used. Only one study assessed linkage by means of a randomised trial. Five studies had data on cotrimoxazole (CTX) prophylaxis and 12 on ART eligibility and initiation. CTX uptake among those eligible ranged from 0% to 100%. The proportion of persons eligible for ART ranged from 16.5% (95% CI, 12.1–21.8) to 77.8% (95% CI, 40.0–97.2). ART initiation among those eligible ranged from 14.3% (95% CI, 0.36–57.9%) to 94.9% (95% CI, 91.3–97.4%). Additional linkage strategies, whilst seeming to increase linkage, were not associated with higher uptake of CTX and/or ART. Most of the studies were susceptible to risk of outcome ascertainment bias. A pooled analysis was not performed because of heterogeneity across studies with regard to design, setting and the key variable definitions. Conclusion: Only few studies from SSA investigated linkage to care among adults newly diagnosed with HIV through HBHCT. Linkage was often low after routine referral but higher if additional interventions were used to facilitate it. The effectiveness of linkage strategies should be confirmed through randomised controlled trials.